Association between childhood adversity and criminal thinking: the role of attachment - Yang, Yang (Psychology, crime & law, 2021)
The current cross-sectional study adopted structural equation modeling (SEM) to examine the association between childhood adversity and criminal thinking, and the role of attachment being a mediator in this relationship, in an offending sample. Data were collected from a sample of 209 inmates (169 of which were male) in a local jail. The results of SEM analyses indicated that childhood adversity was positively associated with attachment anxiety, attachment avoidance, and criminal thinking. Attachment avoidance was positively associated with criminal thinking and mediated the influence of childhood adversity on criminal thinking. Specifically, greater childhood adversity predicted higher attachment avoidance, which in turn was associated with higher levels of criminal thinking. Attachment anxiety did not correlate with criminal thinking; nor did it mediate the influence of childhood adversity on criminal thinking. The findings suggested that childhood adversity and insecure attachment are important risk factors in treating criminal thinking. Practitioners may consider incorporating therapies that facilitate self-reflective functions into offender rehabilitation programs or offer a taste of secure base for justice-involved individuals with childhood adversity.